Successful treatment of Takayasu arteritis with rituximab as a first-line immunosuppressant - O'Connor, Mortimer B (BMJ Case Rep, 2017)
Takayasu arteritis is a rare large vessel vasculitis which has traditionally been treated with high-dose steroids. There have been a small number of publications where biological agents have been used to manage refractory cases. To the authors knowledge, there are no publications using biological agents in combination with steroids as a first-line treatment in Takayasu arteritis. In this publication, we document the case of Takayasu arteritis, in a 39-year-old woman, where rituximab was used in combination with steroids as a first-line agent in the setting of poorly controlled bipolar affective disorder.